Синтез замещенных гидразонов 9-гидрокси-9-флуоренкарбоновой кислоты - Назаров, В. Н.; Марченко, Я. С.; Таран, С. В. (НТУ "ХПИ", 2008)
У статті наведена схема синтезу гидразида 9-гидроксі-9-флуоренкарбоновой кислоти з коксохімічного 9,10-фенантренхінона. Показано використання даного гидразида в реакціях з оксіальдегидами ароматичного ряду. Описано умови синтезу й очищення кінцевих продуктів, які становлять інтерес для вивчення окремих видів біологічної активності.

In the article the chart of synthesis of gidrazid of 9-gidroksi-9-fluorencarbon acid from kokechemical 9,10-fenantrenkhinon is resulted. The use of this gidrazid in reactions with oksialdehyde of aromatic row is shown. The terms of synthesis and cleaning of the finished goods which make intnres for the study of separate types of biological activity are described.
Keywords: гербициды; флуорен; салициловый альдегид; изопропиловый спирт